An examination of anger levels of the individuals doing extreme sport - Fahri Akcakoyun; Merve Ceylan; Vedat Mutlu (Türk Spor ve Egzersiz Dergisi)
This study has been conducted in order to identify the trait angerand the manner of expressing anger of extreme sport participants. “Trait Anger and Anger Expression Scale” that was developed by Spielberger et al. (1983) and adapted to our language by Özer (1994) has been used in the study. The questionnaires have been applied to a total of 175 participants as 121 people doing extreme sport and 54 people doing any sport except for the extreme ones. When the data have been investigated, it is seen that there is a meaningful difference between the participants doing extreme sport and the ones doing team sports in terms of trait anger, control of anger and anger - in. Moreover, it has been observed that there is a meaningful difference between age groups in terms of trait anger and control of anger and also a difference between genders in terms of trait anger levels. When the results of the participants doing extreme sports and doing any other sports have been compared, it is seen that the level of trait anger is lower in the participants doing extreme sport and that they do not bottle up their angers and they can control it easily. Also, it is seen that the level of trait anger is lower between the ages of 22 to 27 and the level of anger is higher in females.